(untitled) (Journal of Pharmaceutical Negative Results, 2022)
“Sustainability” and “Green” have been the biggest buzz words for the past two decades, owing to the environmental and health benefits that these initiatives extend. These have been a topic of research for more than five decades now. With various big organization’s conscious efforts to reduce their carbon foot print many others are following pursuit. Customers are now demanding cleaner products more than ever before and are much more aware of the damages that their habits in past have caused to the environment and indirectly themselves. With the change being reflected in various techniques, practices and methods of production, many organizations are claiming to be sustainable or green worldwide. While the concept has been embraced by various organizations, many retailers around the world are also actively aligning themselves to it. The change is rather slow in India and not much knowledge is there in relation to green retailing amongst the retailers and customers. The Green aspect seems to be restricted to either the product or the method of production. In our research we aim to interact and understand the retailers’ point of view about green retailing, products offered, steps that they take to communicate their efforts to their customers, their efforts towards adopting sustainable ways of production and the impact of all these over retailer preferencescompared to their non green competitors amongst the small green food retailers in tri-city region in India. We used a 50-item structured questionnaire and contacted 100 such retailers telephonically using convenient sampling method. 67 retailers qualified the green retailing criteria, and we received 51 responses. Out of these two responses were not found suitable for analysis and hence kept aside. According to our study the understanding about green retailing in local Indian food industry is ambiguous. Many retailers are trying to use the “green” tag by adapting one of the many ways but not really imbibing the spirit of going green in totality. Sustainability has the strongest correlation with the green retailer performance followed by product attributes.